Osteogenic Differentiation Triggered by Intracellular Magnetoelectric Stimulation of Core–Shell Nanotransducers under Remotely Applied Magnetic Fields; ACS Nano; Vol. 19, iss. 50 - Mendes M. C. Maria; Martins E. A. G. Elisa; Chernozem R. V. Roman Viktorovich; Chernozem P. V. Polina Viktorovna; Custódio C. C. Catarina; Surmenev R. A. Roman Anatolievich; Kholkin A. L. Andrei; Silva A. S. Ana; Mano J. F. João (2025, 2025)
Title screen